2020
DOI: 10.1007/s11469-020-00341-w
|View full text |Cite
|
Sign up to set email alerts
|

Path Analysis of the Relationship Between Optimism, Humor, Affectivity, and Marital Satisfaction Among Infertile Couples

Abstract: Marital satisfaction is an important factor for establishing a family relationship, feeling satisfied, and living happily together. The aim of the present study was to investigate the relationship between optimism, humor, positive and negative affect, and marital satisfaction among infertile couples. The sample comprised 80 infertile Iranian couples (n = 160) who visited infertility clinics. Participants completed a series of Persian versions of psychometric scales related to optimism (Attributional Style Ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 63 publications
(74 reference statements)
1
4
0
Order By: Relevance
“…As predicted, self-enhancing humor was associated with less psychological distress and perceived stress at T1, whereas selfdefeating humor was associated with greater T1 psychological distress and perceived stress. These results are consistent with prior research on the relations of humor styles with well-being under chronic stress (Fritz, 2020b;Fritz et al, 2017;Kerkkanen et al, 2004;Ostovar et al, 2020;Ramirez-Meastra et al, 2020). Surprisingly, affiliative humor was associated with greater psychological distress and perceived stress at T1, which is inconsistent with prior findings.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…As predicted, self-enhancing humor was associated with less psychological distress and perceived stress at T1, whereas selfdefeating humor was associated with greater T1 psychological distress and perceived stress. These results are consistent with prior research on the relations of humor styles with well-being under chronic stress (Fritz, 2020b;Fritz et al, 2017;Kerkkanen et al, 2004;Ostovar et al, 2020;Ramirez-Meastra et al, 2020). Surprisingly, affiliative humor was associated with greater psychological distress and perceived stress at T1, which is inconsistent with prior findings.…”
Section: Discussionsupporting
confidence: 64%
“…Such work is essential to the conceptualization of these constructs: If we are to continue labeling humor styles as "adaptive" and "maladaptive," we must examine how these concepts operate under conditions that require some sort of adaptation. Emerging evidence suggests that the adaptive humor styles do indeed facilitate adjustment to stressors outside of the laboratory, including coping with police work (Kerkkanen et al, 2004), university academics (Fritz, 2020a), chronic pain (Ramirez-Meastra et al, 2020), infertility (Ostovar et al, 2020), and terrorist attacks (Fritz et al, 2017). By contrast, the maladaptive humor styles interfere with adjustment to these same stressors, with a particularly strong pattern of evidence demonstrating that self-defeating humor predicts worse psychological and physical adaptation to stressors over time (Fritz, 2020b;Schneider et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Affectivity is a stable and enduring pattern of behaviors showing positive affect (PA), characterized by active, alert, attentive, determined, enthusiastic, excited, inspired, interested, proud, and strong attributes, and negative affect (NA), characterized by afraid, ashamed, distressed, guilty, hostile, irritable, jittery, nervous, scared, upset attributes, as opposed to the dimensions of a mood state (Watson et al, 2000;Watson & Tellegen, 1985;Zevon & Tellegen, 1982). Researchers who study relationships have reported a strong positive association between PA and relationship satisfaction, suggesting that positive traits provide a framework for the development and maintenance of stable and lasting relationships between couples (Ostovar et al, 2020). To date, relationship satisfaction has been studied specifically in terms of dyadic stress and coping (Badr et al, 2007;Falconier et al, 2015;Iqbal & Safdar, 2014;Lewandowski et al, 2010;Parise et al, 2017); that is, through marital satisfaction (Ostovar et al, 2020;Parise et al, 2019), romantic relationship satisfaction (Vollmann et al, 2019), and marital relationships (Salazar, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Researchers who study relationships have reported a strong positive association between PA and relationship satisfaction, suggesting that positive traits provide a framework for the development and maintenance of stable and lasting relationships between couples (Ostovar et al, 2020). To date, relationship satisfaction has been studied specifically in terms of dyadic stress and coping (Badr et al, 2007;Falconier et al, 2015;Iqbal & Safdar, 2014;Lewandowski et al, 2010;Parise et al, 2017); that is, through marital satisfaction (Ostovar et al, 2020;Parise et al, 2019), romantic relationship satisfaction (Vollmann et al, 2019), and marital relationships (Salazar, 2015). However, the association between affectivity and relationship satisfaction has rarely been investigated with dyadic stress and coping as outcome variables (see Parise et al, 2019), for example, in the Systemic Transactional Model (STM; Bodenmann, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Although marital satisfaction is something very important but strong finding suggests that marital satisfaction tends to decrease toward the increasing age of marriage (Umberson, Williams, Powers, Chen, and Campbell, 2005). Thus, marital satisfaction is an important factor for establishing a family relationship (Ostovar, et al, 2020).…”
Section: Introductionmentioning
confidence: 99%